Empowering consumers to reduce corporate tax avoidance: Theory and experiments - Enrique Fatas; Antonio J. Morales; Axel Sonntag (Institut für Höhere Studien - Institute for Advanced Studies (IHS), 2020)
We analyze corporate tax avoidance in a theoretical model and in a stylized experimental Bertrand setting in which symmetric firms and consumers sell and buy a homogeneous product, when human participants make decisions as firms and consumers. We investigate how market power and information disclosure of firms' tax avoidance behavior impacts corporate tax avoidance and market competition. By imposing a tax rating, corporate tax behavior becomes more transparent, and consumers actively and costly boycott firms that do not pay their taxes. Firms adapt and anticipate consumer boycotts and increase tax payments, and prices. When rating disclosure is voluntary, the positive effect on corporate tax compliance vanishes in large markets.
Keywords: H26; C92; D78; D82; L15; 330; tax avoidance; policy measure; tax rating; transparency; lab experiment